The racial conditioning of our children: ending psychological genocide in our schools - Rutstein, Nathan (The National Resource Center for the Healing of Racism, 2001)
The psychological genocide in our schools -- Tracking and standardized tests: traps for the unaware -- White students are damaged, too -- Taking the crooked path -- The migration of racist beliefs to the "New World" -- Spiritual beings immersed in the human experience -- Principles that can transform education -- Models of educational transformation -- The Imperative restructuring of education -- The Important role of parents in the education of children -- Tools for transformation: the Institute for the Healing of Racism -- The time is ripe.